Gemella Species Bacteremia and Stroke in an Elderly Patient with Respiratory Tract Infection. (2nd January 2017) - Jayananda, Sriraksha; Gollol-Raju, Narasimha Swamy; Fadul, Nada
Abstract : Gemella species are part of normal human flora. They are rarely associated with infections. As opportunistic pathogens, they can cause life-threatening infection in individuals with risk factors. We present an unusual case of an elderly patient, with no predisposing risk factors, who presented with respiratory tract infection and Gemella species bacteremia and suffered a stroke in the absence of features of endocarditis.